Correlation Of Oil Content and Epiphytic Diatom Density in seagrasses Leaves Enhalus acoroides in Rupat Utara Waters Bengkalis Distric Riau Province - Adi Maulana; Yusni Ikhwan; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study were conducted in survey method. Four stations were established with three replication of each sampling station. It revealed that oil content in water ranged from (0.4391 – 0.7973) ppm. The highest epiphytic diatom density on the seagrass leaves oppeared in station 4 which accounted 366 ind/cm2, while the lowest 132 ind/cm2 found in station 2. During the study, epiphytic diatom species most commonly found are Isthmia sp, Navicula sp, Skeletonema sp, Ulothrix sp, dan Synedra sp. Statistical analysis showed the oil content and epiphytic diatom density correlation were weak with coefficient of (0.05)Key words : Rupat Utara Water, Oil Content, Epiphytic Diatom